ТОВАРОЗНАВЧИЙ ПІДХІД ДО ОЦІНКИ ЯКОСТІ ВИНА З ВИКОРИСТАННЯМ ІНТЕЛЕКТУАЛЬНИХ ТЕХНОЛОГІЙ - Fil, Mariya (Zhytomyr Ivan Franko State University, 2025)
The relevance lies in the constant development of the culture of wine consumption, the improvement of methods for its assessment, and the growth of the role of sommeliers as specialists capable of subtly recognizing and interpreting the organoleptic characteristics of a drink. Changes in approaches to tasting, the introduction of new technologies (in particular, electronic tongues), as well as the increase in interest in gastronomic expertise indicate the importance of scientific and practical understanding of the evolution of wine assessment. Holding professional competitions, in particular "The Best Sommelier of Ukraine", actualizes the issue of professionalization of the industry and the formation of new quality standards in winemaking and sommeliers. The purpose of the study is to analyze the evolution of wine assessment methods in the context of modern sommelier practices and the impact of technological innovations on wine tasting. To achieve this goal, the following methods were used: comparative analysis of traditional and modern tasting techniques; methods of organoleptic research, which include the assessment of visual, aromatic and taste characteristics of wine; content analysis of materials from international and national sommelier competitions; as well as the study of modern scientific developments, in particular the technology of the "electronic tongue". It was determined that modern sommelier practice is based on a phased analysis of wine: visual, aromatic, taste and aftertaste. In particular, aroma is recognized as a key factor in the differentiation of wines, but it is the taste qualities that allow us to identify the true origin of wine - terroir or industrial. The study also confirmed the effectiveness of using innovative technologies, such as an electronic tongue, which, thanks to artificial intelligence, is able to accurately classify wines and form recommendations for their combination with food. The study showed that approaches to wine tasting have undergone significant changes, adapting to new market requirements and technological progress. Traditional wine evaluation, which was previously based mainly on its aromatic characteristics, is now supplemented by the analysis of texture, acidity and aftertaste. The importance of objective tools, such as sensory devices and electronic tasting systems, is growing, allowing for greater accuracy and consistency of evaluation. At the same time, wine tasting remains an art in which personal impressions and cultural contexts play an important role. Scientific novelty. The study proposes an updated approach to the analysis of wine tasting, which combines sensory evaluation with elements of modern technologies. For the first time, emphasis is placed on the integration of objective tools (for example, electronic sensors) into the process of evaluating the organoleptic characteristics of wine